Evaluation of Seasonal Inactivated Influenza Vaccines Prophylactic Efficacy - K. V. Zhdanov; K. Kasyanenko; O. V. Mal'cev; N. I. L'vov; D. A. Lioznov; I. I. Lapikov; K. S. Ivanov (Эпидемиология и вакцинопрофилактика, 2022)
Relevance. Seasonal flu vaccination is still the most effective way to protect against flu viruses and help to reduce the burden of flu illnesses. Another possible benefit is the impact of yearly vaccines on severity of breakthrough infection. In this regard, the issue of choosing safe vaccine with high immunogenicity becomes relevant.Aims. To evaluate the prophylactic efficacy of inactivated seasonal flu vaccines (quadrivalent subunit vaccine with adjuvant and trivalent vaccine) and reactogenicity of quadrivalent vaccine.Materials and methods. 491 cases were included in our study: 152 cases received adjuvanted quadrivalent subunit flu vaccine «Grippol Quadrivalent», 118 cases received trivalent inactivated flu vaccine and 221 cases who have received no vaccinations during 2018–2019 epidemic season.Results. inactivated vaccines showed high prophylactic efficacy in preventing seasonal influenza. Incidence of influenza and other viral respiratory disease cases was lowest in «Grippol Quadrivalent» group. Breakthrough influenza cases in individuals vaccinated with inactivated vaccine were predominantly mild, no severe cases were reported. The early post-vaccination period in «Grippol Quadrivalent» group showed no variation in adverse events with other vaccines.Conclusion. Adjuvanted quadrivalent subunit flu vaccine was the most efficacious in preventing influenza in 2018–2019 epidemic season.